Access to justice for persons with disabilities: a “Toothless tiger”? - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (2018)
Persons with Disabilities (PWD) are subject to adverse stigma and discrimination from the society. Through these experiences, there is the mandatory requirement for the State to create conducive and appropriate measures which allow their access to justice within the legal system. The measures including the ratification of the CRPD, the Convention under United Nations specifically for PWD and local legislations confirm to the standard stipulated under CRPD. The Malaysian Persons with Disabilities Act 2008, however, has been criticised for no penalty mechanism which made it ‘toothless tiger’ lead to discriminate their ability to access to justice. This paper will analyse the access to justice available for PWD within international and domestic legal framework. This analysis would improve the laws and create an avenue to create awareness on their rights to access to justice within the legal system. The final analysis showed that it is crucial for the State to ensure protection available for this minority group in access to the justice system which would enhance and promote their rights at the highest level.